Evolutionary patterns of mandible shape diversification of caviomorph rodents - Alvarez, Alicia (2020)
Caviomorphs are a mainly South American rodent clade with high taxonomic and ecomorphological diversity. In this study, we combine geometric morphometric, functional, ancestral reconstruction, and macroevolutionary analyses to quantify the magnitude, direction, and rates of shape diversification of the caviomorph mandible, and to explore the morpho-functional implications and potential ecological catalysts of the observed shape changes. The mandible shape was significantly related to habits and size, and had a better fit with an evolutionary model where the main clades occupy distinct adaptive peaks. The morphological evolution of octodontoids is characterized by pulses of rate acceleration, but without reaching high disparity. Such pulses are mainly linked to the acquisition of fossorial specializations, including short and robust mandibles, and the increasement of forces at incisors. Conversely, derived cavioids show slower but continuous shape changes that allowed them to reach the most divergent, grazing morphologies in which slender mandibles with more marked antero-posterior movements for grinding action are favored. Interestingly, the major morphological changes occurred mainly during the early Oligocene and lower late Miocene, two time periods that involved global climatic events and strong changes in the vegetational structure of South America. The evolution of octodontoid and cavioid mandibles seems to be related to the occupation of subterranean and epigean niches, respectively, in the progressively expanded Cenozoic open landscapes of southern South America.